Location location location: A carbon footprint calculator for transparent travel to COP27 - Anthony Costello; Jacqueline McGlade; Jhénelle A Williams; Jonathan Barnsley; Mark Maslin; Matthew Winning; priti parikh; Richard Taylor; Simon Chin-Yee (UCL Open Environment, 2023)
Addressing the large carbon footprint of conferences such as the UN Climate Change Convention Conference of the Parties (COP) will be important for maintaining public confidence in climate policy. Transparency is also a vital aspect of creating equitable outcomes in climate policies, as often those most likely to be affected or who are able to create change on the ground are often unable to attend in person because of the high financial costs as well as having a large carbon footprint. The selection of host locations for the regular meetings of the UN Climate Change Convention is based on a rotation in amongst the five UN regions, which for 2022 is Africa. Here, we present UCL’s own carbon footprint calculator and use it to weigh the benefits of certain modes of transport to the 2021 COP 26 in Glasgow, UK and the 2022 COP 27 to be held in Sharm El-Sheikh, Egypt. The calculator demonstrates the well-known carbon-efficiency of coach and rail over flights, but shows that these benefits are only partly mitigated in the case of COP 27 due to insufficient transport links from Europe to the conference location. However, we also highlight some of the benefits of hosting a COP in the global South, particularly in the context of climate justice. Incorporating these principles into the calculator, we invite visitors to COP this year to carefully consider their options for carbon offsetting and how the tenets of climate justice could be integrated into the carbon accounting framework.